Cognitive contextualization of interactivity: Una mirada desde los objetos tecnológicos de aprendizaje - García-Mora, Jhon Jairo; Patiño-Jaramillo, Margarita Emilia; Moreno-Jiménez, Sonia Jaquelliny (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
In this paper we present the result of a documentary research that allowed the cognitive contextualization of interactivity supported by the activity theory as a holistic perspective of human activity. Cognitive contextualization of interactivity seeks to provide fundamentals for the design of Interventive Learning Objects (ILO) from the cognitive processes of Marzano and Kendall's taxonomy, analyzing the categorical structures of an interactive design and the elements that intervene in the mental processes that generate learning during interactivity: the activation of memory and the transformation of the information captured during the interventive process during interactivity.